2022
DOI: 10.7554/elife.75046
|View full text |Cite
|
Sign up to set email alerts
|

A crowd of BashTheBug volunteers reproducibly and accurately measure the minimum inhibitory concentrations of 13 antitubercular drugs from photographs of 96-well broth microdilution plates

Abstract: Tuberculosis is a respiratory disease that is treatable with antibiotics. An increasing prevalence of resistance means that to ensure a good treatment outcome it is desirable to test the susceptibility of each infection to different antibiotics. Conventionally this is done by culturing a clinical sample and then exposing aliquots to a panel of antibiotics, Using 96-well broth micro dilution plates with each well containing a lyophilised predetermined amount of an antibiotic is a convenient and cost-effective w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…15 The plates were read manually by diagnostic laboratory scientists, by the automated reading software Automated Mycobacterial Growth Detection Algorithm, 16 and by a citizen science project (BashTheBug) for additional verification. 17 Procedural details of MIC testing are provided in appendix 1 (pp 4–5 ).…”
Section: Methodsmentioning
confidence: 99%
“…15 The plates were read manually by diagnostic laboratory scientists, by the automated reading software Automated Mycobacterial Growth Detection Algorithm, 16 and by a citizen science project (BashTheBug) for additional verification. 17 Procedural details of MIC testing are provided in appendix 1 (pp 4–5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple projects to date have demonstrated that citizen scientists can be effectively engaged in a wide variety of biological image analysis tasks, such as the tracing of connected neurons through electron microscopy (EM) data in Eyewire (Kim et al, 2014), clicking on protein particles in cryo-EM data in Microscopy Masters (Bruggemann et al, 2018), and scoring tumor markers in pathology samples in Cell slider (Dos Reis et al, 2015), amongst others (Smittenaar et al, 2018;Ørting et al, 2019;Benhajali et al, 2020;Fisch et al, 2021;Fowler et al, 2022). The efficacy of applying online citizen science for the analysis of biological image data, both as an avenue for producing novel research and as a powerful tool for public engagement, has led to a rise in interest from the biological volumetric imaging research community in applying this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Citizen science collaborations between volunteers and research teams can play an important role in educating the public about scientific concepts and have been instrumental in recognizing complex patterns within biological data, starting with research in ecology and extending to various biological fields, including protein folding, DNA sequence alignment, electron microscopy, and microbiology [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…A previous project hosted on Zooniverse, Bash the Bug 7 , successfully engaged citizen scientists to look at images of bacterial growth and identify their resistance to antimicrobial drugs. This demonstrated how citizen science can be used for antimicrobial resistance research and the development of novel diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation